Alpha-tubulin promoter from Chlorella vulgaris allows genetic transformation of green coccoid microalga - Raquel Fernández-Rodríguez; Giovanni Garro-Monge; Maritza Guerrero-Barrantes; Olman Gómez-Espinoza (Tecnología en Marcha)
Microalgae have become a feasible platform for high-value recombinant protein production. Although diverse sets of genetic tools for microalgae transformation have been developed, some critical elements, such as endogenous promoters, need to be improved for increasing transgene expression levels after genetic transformation. This work aims to evaluate a sequence from the 5′ upstream region of the alpha-tubulin gene from Chlorella vulgarisas a promoter for the expression of an antibiotic resistant gene in Chlorella sorokiniana. Using in silicoanalysis it was possible to identify a proximal promoter corresponding to 281 nucleotides upstream of the ATG start codon, which possessed 9 potential cis-regulatory element, including TATA Box and CAAT Box. The proximal promoter sequencewas used to drive the expression of a streptomycin-resistance gene (aada), previous optimization of its codon usage. The codon optimization of the aadasequence allowed it to obtain a GC content of 69.8% (compared to 53% of the original sequence), which increases its similarity with Chlorellasp. genomes (67.2%). Both genetic elements were cloned into the pUC57-Kan vector and transformed into C. sorokiniana cells by electroporation. The microalgae transgenic colonies were identified through culture in selective medium and PCR. Our results proved the capacity of the Chlorella vulgaris alpha-tubulin promoter to express a foreign antibiotic-resistance gene in C. sorokinianacells. Research of endogenous promoting sequences is essential in order to accomplish an efficient heterologous gene expression, especially in microalgae used for industrial production like those from Chlorella genus.